DAMPAK PANDEMI COVID-19 TERHADAP PENGGUNAAN E- BANKING PADA UMKM DI KECAMATAN LABUHAN BADAS KABUPATEN SUMBAWA - Sri Rahayu; I Putu Gede Diatmika; Ika Fitriyani (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study aims to determine the impact of the Covid-19 pandemic on the use of E-Banking on UMKM in Labuhan Badas District, Sumbawa Regency. Qualitative research with Phenomenology: a form of qualitative research in which the researcher attempts to understand how one or more individuals experience a phenomenon, through case studies and primary data sources. The results showed that there were 52 UMKM actors in Labuhan Badas District. The Covid-19 pandemic has an impact on the decline in the income of UMKM actors in Labuhan Badas District, Sumbawa Regency, this affects the decision of UMKM actors to use E-Banking services. Another obstacle is also caused by the lack of understanding, knowledge and information related to E-Banking services which has resulted in UMKM actors in Labuhan Badas District, Sumbawa Regency not yet optimal in using E-Banking services.